Series and Summations on Binomial Coefficients of Optimized Combination - Chinnaraji Annamalai; Junzo Watada; Vishnu Narayan Mishra (The Journal of Engineering and Exact Sciences)
This paper presents innovative series and summations derived from the optimized combinations relating to the combinatorics. These series and summations will be useful for the researchers who are involving to solve the scientific problems.